A comparative analysis of torque ripple reduction techniques for sensor BLDC drive - Karthika Mahalingam; Nisha Kandencheri Chellaiah Ramji (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Brushless direct current motors (BLDC) are prominent due to their high efficiency and less maintenance. However, BLDC motor applications are limited due to the requirement of a complex controller, the existence of torque ripple, and high cost. This research work describes the comparative analysis of different control strategies of torque ripple reduction in BLDC motors and it discusses various topologies viz. cuk converter, simple voltage modulator scheme, charged capacitor, Z-source inverter, and Quasi- Z source inverter-based toque ripple reduction techniques. The effectiveness of different control strategies has been verified using MATLAB Simulink and it helps to understand different control strategies for torque ripple reduction during the entire speed range. The analysis of MATLAB results reveal that the voltage modulation scheme reduces the torque ripple considerably during the entire speed range along with the noise- less operation of the BLDC motor when compared with other topologies.